High-rate electrode material 2LiFePO4·Li3V2(PO4)3@carbon/graphene using the in situ grown Fe4(VO4)4·15H2O precursor on the surface of graphite oxide. Issue 41 (7th May 2015) - Zhang, Bao; Li, Hui; Zhang, Jia-feng
<x xml:space="preserve">Abstract</x> 2LiFePO4·Li3V2(PO4)3@carbon/graphene (2LFP·LVP@C/G) as a cathode material, based on an in situ grown Fe4(VO4)4·15H2O precursor on the surface of graphene oxide, was synthesized by a solid-state process.